Perwalian Anak Yatim dalam Al-Qur’an: Analisis Tafsir Maudhu’i - Putri Rahma; Sukiati; Fatimah (Al Fuadiy Jurnal Hukum Keluarga Islam, 2026)
Guardianship of orphans constitutes a fundamental legal institution within Islamic law, yet existing studies often remain normative and fragmented in their treatment of Qur’anic sources. This article presents a thematic interpretation of Qur’anic legal verses related to orphan guardianship in order to construct a coherent and systematic conceptual framework. Relevant verses dispersed across multiple chapters are examined through a maudhu’i (thematic) approach, taking into account contextual background, inter-verse relations, and the objectives of Islamic law. The analysis reveals that the Qur’an establishes orphan guardianship on the principles of trust (amanah), justice, public welfare, and accountability, with particular emphasis on the protection of property and the gradual development of the child’s legal and economic capacity. The guardian is positioned as a trustee with limited and temporary authority rather than an absolute holder of power. The obligation to transfer property upon the attainment of maturity and sound judgment (rusyd) underscores guardianship as a transitional legal mechanism oriented toward autonomy rather than dependency. These findings demonstrate that orphan guardianship in the Qur’an functions as a structured legal institution grounded in substantive justice, not merely moral exhortation. This article contributes to the field of Qur’anic legal studies by offering a thematic synthesis that is both conceptually rigorous and relevant to contemporary discussions on Islamic family law and child protection.